2023
DOI: 10.3390/atmos14060969
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Effect of International Maritime Regulations on Air Quality in the Southern North Sea

Abstract: Air pollution is a leading cause of death worldwide, and it has a profound impact on the planet’s climate and ecosystems. A substantial portion of air pollution is attributable to Ocean Going Vessels (OGVs). In light of this, international regulations have been put in place to mitigate air pollutant emissions from OGVs. While studies have indicated that these regulations can create significant health, environmental, and economic benefits, there remains a research gap regarding their specific impact on enhancin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 41 publications
(77 reference statements)
0
0
0
Order By: Relevance
“…The examination of the Belgian data reveals that the mean NO x emissions are not decreasing as anticipated with the implementation of stricter emission limits. On the contrary, the data indicates that NO x emissions are increasing 24,29 . Furthermore, non-compliance levels for NO x emissions are also rising 24,29 .…”
Section: No X Emission Control Areamentioning
confidence: 88%
See 1 more Smart Citation
“…The examination of the Belgian data reveals that the mean NO x emissions are not decreasing as anticipated with the implementation of stricter emission limits. On the contrary, the data indicates that NO x emissions are increasing 24,29 . Furthermore, non-compliance levels for NO x emissions are also rising 24,29 .…”
Section: No X Emission Control Areamentioning
confidence: 88%
“…Despite the fact that the above-mentioned publications projected signi cant health bene ts from the implementation of international maritime emission regulations and that emissions models predict a decrease of air pollution from shipping 22,23 , there still remains a research gap regarding the effectiveness of the established international regulations in reducing real-world emissions from OGVs in the wider ECAs. At the national level, Van Roy et al showed varying results of the success of international regulations to improve air quality in Belgium 24 .…”
Section: Introductionmentioning
confidence: 99%
“…The preliminary feasibility of a particular waste recycling technology [85] Pollution from ships-oil -Issues related to the identification and prevention of ship pollution, with special focus on oil pollution [86] -Issues related to pollution caused by oil spills into the sea, analyzing some major marine pollution incidents [87,88] -Various aspects of both land-and sea-based oil pollution [89] -Results of research based on a fact that over a million tons per year of oil is spilled from ships into the sea [90] -Adequacy level of the MARPOL convention implementation related to the pollution of the sea by oil from ships [91,92] Pollution from ships-solid and liquid waste -The marine pollution caused by marine domestic waste [93] -Issues related to the implementation of international regulations (mainly MARPOL convention) for the control of pollution of the sea with solid and liquid waste from ships [94][95][96][97] Pollution from ships-emissions -A fact that pollution from ships is not limited to the sea; it causes significant air and other forms of pollution [98] -The international regulations on ship emissions and their influence on level of SO 2 emissions from Ocean Going Vessels (OGVs) [99] -Summarizing studies that address air pollution, with special focus on particulate matter from marine vessels [100] -Pollution of air by large ships in the hub ports (taking into account that low-grade marine fuel oil contains 3500 times more sulfur than road diesel) [101] -Public health and climate impacts of low-sulfur fuels in global shipping [102] -The status of pollution mitigation measures implemented to date in the shipping sector [103] -The contributions of ship emissions of NO 2 , SO 2 , PM 10 , and PM 2.5 to air quality in the ports [104] -Annex VI (of the MARPOL convention) issues (influence of shipping industry on climate change) [105,106] -Initial strategy for the reduction in GHG emissions from ships in a port [107] -Air quality management in main Mediterranean ports [108] (Source: author).…”
Section: Research Problem Referencementioning
confidence: 99%
“…The research whose results are shown in the analyzed literature covers a very wide geographical area: developing countries [61,70], Indonesia [65], India [71], Nigeria [74,84], China [76], Malaysia [77], the world ocean [78,86], the Arctic region [80], Cambodia [89], Vietnam, the USA, Australia [94], the Southern North sea [99], Hong Kong [101], the Mediterranean sea [104,108], Kenya [105], and the Caspian sea [107]. Obviously, the references analyzed in Table 4, as per the related geographical areas, cover almost all continents and the world ocean and indicate what the priorities are in the domain of the prevention of pollution from ships in those areas.…”
Section: Research Problem Referencementioning
confidence: 99%
See 1 more Smart Citation